Determinasi Hambatan Penerapan Konsep Green Building pada Proyek Konstruksi di Indonesia Timur - Glady Oei; Nectaria Putri Pramesti (Jurnal Talenta Sipil, 2026)
Global climate change encourages the implementation of the green building concept as a strategy to reduce greenhouse gas emissions in the construction sector. However, its implementation in the Eastern Indonesia region still faces various obstacles. This study aims to analyze the influence of barrier factors on the level of barriers to the implementation of the green building concept and to identify the most dominant factor. The approach used is quantitative with an explanatory research design. Data were collected through questionnaires from 94 respondents consisting of contractors and consultants in Eastern Indonesia. The analysis was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results show that technical, educational, economic, and technological factors have a significant effect on the level of barriers to green building implementation, while regulatory factors do not have a significant effect. The economic factor becomes the most dominant barrier, indicated by the highest path coefficient value compared to other variables. These findings indicate that the aspects of initial investment costs and limited financing remain the main considerations in the implementation of green building in the region. Academically, this study enriches the study of barriers to green building implementation in Eastern Indonesia, which is still limited, while also strengthening the use of SEM-PLS in structural model analysis in sustainable construction studies.